Eutanásia e suicídio assistido: o Direito entre O Escafandro e a Borboleta - Fernanda Otero Costa (2016)
The research discusses euthanasia and assisted suicide, which are legally typified as criminal conducts in Brazil. The study departs from an analysis of the books O Escafandro e a Borboleta, from Jean-Dominique Bauby, and Cartas do Inferno, from Ramón Sampedro, to scrutinize the meaning of what is considered to be sacred and holy both in Religion and Law. The aim of this study is to conceptually restructure the notion of life as a protected legal interest that embodies both the ideas of the life given and the life built. This restructuration, thus, might provide people a space of choice to make free and responsible decisions concerning the way and how long they want to live.